2006
DOI: 10.3354/dao071119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic markers associated with Gyrodactylus salaris resistance in Atlantic salmon Salmo salar

Abstract: Gyrodactylus salaris Malmberg, 1957 is a freshwater monogenean ectoparasite of salmonids, first recorded in Norway in 1975 and responsible for extensive epizootics in wild Atlantic salmon Salmo salar L. The susceptibility of different populations of Atlantic salmon to G. salaris infection differs markedly, with fish from the Baltic being characterised as relatively resistant whereas those from Norway or Scotland are known to be (extremely) susceptible. Resistance to Gyrodactylus infection in salmonids has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 35 publications
2
38
1
1
Order By: Relevance
“…mbb.sfu.ca/GRASPlinkage.html), which combines molecular marker and mapping data from the Genomic Research on Atlantic Salmon Project (GRASP) (http:// grasp.mbb.sfu.ca/), the Salmon Genome Project (SGP) (http:/ /www.salmongenome.no/cgi-bin/sgp.cgi), and the European Union collaborative SALMAP project (http:/ / www.salmongenome.no/cgi-bin/sgp.cgi). These maps have facilitated the detection of QTL in salmon affecting body weight and condition factor (Reid et al 2005), while molecular markers have also been linked to disease resistance against infectious salmon anemia (ISA) (Grimholt et al 2003;Moen et al 2004bMoen et al , 2007, furunculosis (Grimholt et al 2003), and the ectoparasite Gyrodactylus salaris (Gilbey et al 2006). Furthermore, in the closely related rainbow trout, two QTL have been identified with a highly significant effect on freshwater IPN resistance in a backcross family (Ozaki et al 2001).…”
Section: Nfectious Pancreatic Necrosis (Ipn) Is a Viral Dis-mentioning
confidence: 99%
“…mbb.sfu.ca/GRASPlinkage.html), which combines molecular marker and mapping data from the Genomic Research on Atlantic Salmon Project (GRASP) (http:// grasp.mbb.sfu.ca/), the Salmon Genome Project (SGP) (http:/ /www.salmongenome.no/cgi-bin/sgp.cgi), and the European Union collaborative SALMAP project (http:/ / www.salmongenome.no/cgi-bin/sgp.cgi). These maps have facilitated the detection of QTL in salmon affecting body weight and condition factor (Reid et al 2005), while molecular markers have also been linked to disease resistance against infectious salmon anemia (ISA) (Grimholt et al 2003;Moen et al 2004bMoen et al , 2007, furunculosis (Grimholt et al 2003), and the ectoparasite Gyrodactylus salaris (Gilbey et al 2006). Furthermore, in the closely related rainbow trout, two QTL have been identified with a highly significant effect on freshwater IPN resistance in a backcross family (Ozaki et al 2001).…”
Section: Nfectious Pancreatic Necrosis (Ipn) Is a Viral Dis-mentioning
confidence: 99%
“…Also, due to the outbred nature of the families, it would be expected that most parents would not be informative for most markers and that the associations, therefore, were family-specific. Furthermore, it points to polygenic control of disease resistance, as found in other studies (Gilbey et al 2006, Barroso et al 2008, with the likelihood that loci with useful variation in mounting an immune response vary among families.…”
Section: Discussionmentioning
confidence: 74%
“…A basic, single marker-single linkage group approach was used (Gilbey et al 2006), whereby microsatellite markers were chosen to cover each linkage group of the linkage map of Gilbey et al (2004), along with further markers from the linkage groups identified in SALMAP (www.asalbase.org/ sal-bin/index) and Moen et al (2008). Furthermore, a growth hormone gene marker, not mapped to any identified linkage group, was screened to assess association with this region of the genome.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Bacteria disease for which QTL resistance traits have been identiied include coldwater disease in rainbow trout [187], Aeromonas hydrophila in rohu (Labeo rohita) [188], Vibrio anguillarum in Japanese lounder [189], Flavobacterium psychrophilum in rainbow trout [190] and pastuerellosis in Gilhead seabream [191]. As for parasitic diseases, QTL resistance traits have been identiied for Gyrodactylus salaris in Atlantic salmon [192] and Monohenean parasite (Benedenia seriolae) in Yellow tail (Seriola quinqueradiata) [193].…”
Section: Applications Of Rna-seq and Omics Strategies -From Microorgamentioning
confidence: 99%